REPROCESSING OF Lc IN IRRADIATED ATMOSPHERES OF UNEVOLVED COMPANIONS IN PRECATACLYSMIC BINARIES (PCB) AS A SENSITIVE TOOL OF MEASURING THE TEMPERATURES OF HOT SUBDWARF PRIMARIES - Pustylnik, I.; Pustynski, V.; Kubat, J. (Одеські астрономічні публікації, 2017)
We report results of modeling physical processes in the outermost layers of strongly irradiated atmospheres of low mass companions in PCBs where Lc radiation coming from the hot subdwarf (sdw) primary is reprocessed. We solve explicitly a set of equations of hydrostatic, ionization and thermal equilibrium and calculate the intensity of reprocessed emergent radiation in recombinations for optically thin plasma. For purely hydrogenic atmosphere and typical for PCBs values of incident densities, gas pressures of irradiated upper atmospheric layers we find that Lc will be absorbed and re-emitted in recombinations within the column of effective thickness (10 6 - 10 8 )cm of HII depending on the electron density and the effective temperature of sdw. The most interesting and non-trivial result of our model computations lies in the overheating of the uppermost layers of irradiated atmosphere: the equilibrium temperature of gas turns out to be considerably higher than the value of radiative temperature in the black body approximation following from the total irradiating of the diluted incoming radiation of sdw. This result enables one to explain the abnormally high values of albedos following from the conventional analysis of the light curves of PCBs (amplitudes of the light curves correspond to albedo values typically amounting to 3 - 5 for well studied systems like V 477 Lyr). The effect of overheating is determined solely by the effective temperature of irradiating source. Thus, we indicate how the effect of reprocessing of Lc radiation can be used as a sensitive tool for a more rigorous determination of the effective temperature of the sdw primaries in PCBs.